Bearing behaviour of aluminium sub-heads with removable beads in façade systems. (August 2021) - Akbari, Masoumeh; Gunalan, Shanmuganathan; Gilbert, Benoit P.; Guan, Hong; Baleshan, Balachandren
Abstract: Occupying a substantial proportion of the overall building expense, building envelopes are the subject of ongoing research and improvement in both aesthetic and structural aspects. The aluminium window wall frame, consisting of vertical members (mullions) and horizontal members (head and sill transoms), is placed between sub-heads at the top and sub-sills at the bottom of the wall. These window walls are designed to carry lateral wind loads. Of particular importance to design stability is the bearing behaviour of aluminium sub-heads. The bearing behaviour and capacities of C-shaped sub-heads were recently investigated through a detailed experimental study at Griffith University for the development of strength prediction equations. To allow for easier assembly of façade panels, a kind of sub-head section known as sub-head with removable bead is used in aluminium window wall system. Two parts of this sub-head are connected together without any external mechanisms. The present research places emphasis on assessing the bearing behaviour of aluminium sub-heads with removable beads through comprehensive experimental testing. A total of 36 tests were conducted using six section geometries, two engagement lengths, and three bearing widths. The bearing strengths obtained from tests of aluminium sub-heads with removable beads were compared with the bearing capacities predicted using the design rules developed by the authors for conventional C-shaped aluminium sub-heads and available cold-formed steel design provisions (AISI S240 2015, TI 809-07, and SSMA 2000 specifications). As a result of the investigation, the current design equations were found to be unreliable for estimating the bearing capacity of aluminium sub-head sections with removable beads. Hence, new design expressions have been developed which accurately predict the strengths of aluminium sub-heads with removable beads under out-of-plane loads. Furthermore, the influence of the removable beads on the bearing behaviour and capacity is discussed in detail.